Погребения эпохи Золотой Орды в сырцовых оградках на территории Центрального Предкавказья - Бабенко, В.А. (Степи Европы в эпоху средневековья, 2012)
The paper considers adobe constructions (fences) located on the territory of the Central Ciscaucasia (Zolotariovka 5, barrow 4, Sovruno 1, barrow 1 (constructions 1 and 2), and Sharakhalsun 5, barrow 8) and studied during excavations of the State Unitary Enterprise “Naslediye” on the territory of Ipatovsky and Apanasenkovsky regions of Stavropol Territory.